Music students' experienced workload, livelihoods and stress in higher education in Finland and the United Kingdom. (19th October 2020) - Jääskeläinen, Tuula; López-Íñiguez, Guadalupe; Phillips, Michelle
ABSTRACT: Neoliberal education policies – viewing students' life as human capital, economic investment for the labour market and consumer power – may increase students' workload in higher education. In this mixed methods study, we examined music students' experiences of workload in Finland and the United Kingdom in connection with stress and livelihoods. We used Bayesian mixed effects ordinal probit regression modelling to estimate effects of countries and livelihoods as predictors for music students' experienced workload in relation to their main subject of study (or principal study) and stress. We analysed music students' lived experiences of workload to find further predictors for the developmental work in universities and educational policies. Results indicate that where neoliberal university culture impacts on music students' livelihoods alongside their studies, this is likely to increase stress but not necessarily impact on the workload associated with their main subject of study. However, stress has a notable effect on students' experiences of workload. We suggest paying attention to certain aspects in universities in relation to workload, such as the gap between well-off students compared to low-income students who need to work, and stress, particularly with female and non-binary gender students. Furthermore, we propose alternative ways to navigate neoliberal university culture.